2002
DOI: 10.1016/s0735-1097(01)01794-6
|View full text |Cite
|
Sign up to set email alerts
|

Removal of cardiodepressant antibodies in dilated cardiomyopathy by immunoadsorption

Abstract: Cardiac autoantibodies play a functional role in DCM, and their removal may induce early hemodynamic improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
126
1
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 173 publications
(139 citation statements)
references
References 26 publications
6
126
1
6
Order By: Relevance
“…Rather than these antibodies, anti-M 2 R antibodies are likely involved in the disease process. Anti-M 2 R IgG decreased the amplitude of transient (Ca 2+ ) i in neonatal rat ventricular cardiomyocytes, which is consistent with the results obtained with the IgGs purified by IA columns from DCM patients' sera [26] and the effects of anti-M 2 R antibodies on guinea pig cardiomyocytes [35]. The antibodies had specificity for M 2 R because a selective M 2 R antagonist AF-DX 116 as well as a synthetic M 2 R peptide blocked the activity.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Rather than these antibodies, anti-M 2 R antibodies are likely involved in the disease process. Anti-M 2 R IgG decreased the amplitude of transient (Ca 2+ ) i in neonatal rat ventricular cardiomyocytes, which is consistent with the results obtained with the IgGs purified by IA columns from DCM patients' sera [26] and the effects of anti-M 2 R antibodies on guinea pig cardiomyocytes [35]. The antibodies had specificity for M 2 R because a selective M 2 R antagonist AF-DX 116 as well as a synthetic M 2 R peptide blocked the activity.…”
Section: Discussionsupporting
confidence: 90%
“…Whereas the thinning of the left ventricle wall, a common finding in DCM patients, was not observed in this model, echocardiograms showed contractile dysfunction along with chamber dilatation, which may represent an early stage of DCM. It has been unclear whether the production of autoantibodies against M 2 R in DCM patients is a result of inflammatory responses or whether such antibodies are pathogenic and actively participate in the disease progression [26][27][28][29]. Our present findings strongly suggest that the anti-M 2 R antibodies participate in the electrical remodeling of left ventricular muscles and subsequently lead to DCM-like cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…These antibodies induce a negative inotropic effect in isolated rat cardiomyocytes through depression of calcium transients; they are furthermore detectable in the majority of DCM patients [15,17]. Recent in vitro data indicate that these antibodies belong to the IgG-3 subclass [16].…”
Section: Discussionmentioning
confidence: 99%
“…Animal models have shown that DCM can be triggered by autoantibodies [8][9][10][11]. Recent clinical studies indicate that cardiac antibodies may play an active role in the pathogenesis and progression of the disease in humans: removal of antibodies by immunoadsorption (IA) induces hemodynamic improvement and ameliorates myocardial inflammation in patients with DCM [12][13][14][15][16][17]. Elimination of cardiodepressant antibodies may be one explanation for the beneficial hemodynamic effects of IA in patients with DCM [15][16][17].…”
Section: Introductionmentioning
confidence: 99%